2018
DOI: 10.1016/j.neurobiolaging.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of functional circuitry in aging brain and the impact of mutated APP expression

Abstract: Alzheimer's disease (AD) is a disease of aging that results in cognitive impairment, dementia, and death. Pathognomonic features of AD are amyloid plaques composed of proteolytic fragments of the amyloid precursor protein (APP) and neurofibrillary tangles composed of hyperphosphorylated tau protein. One type of familial AD occurs when mutant forms of APP are inherited. Both APP and tau are components of the microtubule-based axonal transport system, which prompts the hypothesis that axonal transport is disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(77 citation statements)
references
References 77 publications
(169 reference statements)
5
72
0
Order By: Relevance
“…Similar study of Mn 2+ injection into the CA3 region of the hippocampus in APPSwInd transgenic mice, that express mutant APP with both Swedish and Indiana mutations, showed decreased Mn 2+ transport along the hippocampus to basal forebrain pathway with ageing and altered Mn 2+ accumulation in APPSwInd mice that displayed Aβ plaques. This suggest that the natural alteration in neuronal connections with ageing is further disrupted with APP overexpression and the formation of Aβ plaques (Bearer et al, 2018). In addition, MEMRI was used to assess therapeutic reagents and test their ability to improve axonal transport.…”
Section: Memri In Animal Models Of Neurodegenerationmentioning
confidence: 99%
“…Similar study of Mn 2+ injection into the CA3 region of the hippocampus in APPSwInd transgenic mice, that express mutant APP with both Swedish and Indiana mutations, showed decreased Mn 2+ transport along the hippocampus to basal forebrain pathway with ageing and altered Mn 2+ accumulation in APPSwInd mice that displayed Aβ plaques. This suggest that the natural alteration in neuronal connections with ageing is further disrupted with APP overexpression and the formation of Aβ plaques (Bearer et al, 2018). In addition, MEMRI was used to assess therapeutic reagents and test their ability to improve axonal transport.…”
Section: Memri In Animal Models Of Neurodegenerationmentioning
confidence: 99%
“…To define mechanisms of hyperexcitability and the role of the cholinergic neurons further, it seems useful to focus attention on the DG for several reasons. First, several neuroanatomical changes occur in the DG in hAPP mouse models (Bearer et al, 2018; Fontana et al, 2017; Jacobsen et al, 2006; Krezymon et al, 2013; Ohm, 2007; Palop et al, 2005; Palop et al, 2007; Palop et al, 2003; Roberson et al, 2011; You et al, 2017) that also occur in human AD (Ohm, 2007; Scharfman, 2012; Scharfman, 2019). Regarding hyperexcitability, the DG is relevant because it is considered to be a region that can generate seizures in temporal lobe epilepsy (Heinemann et al, 1992; Kobayashi and Buckmaster, 2003; Krook-Magnuson et al, 2015; Lothman et al, 1992; Scharfman, 2019; Sun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mn 2+ transport along the hippocampus to the basal forebrain pathway was decreased with aging, and the decrease was more pronounced in aged APP SwInd transgenic mice. Thus, with aging, the natural degeneration of neurons is further aggravated by APP overexpression and Aβ plaque formation (112). Medina et al studied the mechanism underlying the decrease in axonal transport and found that knockout of microtubule motor kinesin light chain-1 (KLC-1) decreases Mn 2+ transport from the hippocampus to the forebrain, but this effect is weak (39), and other kinesins or motor molecules may also play a role in axonal transport.…”
Section: Neurodegenerative Diseases Alzheimer's Disease (Ad)mentioning
confidence: 99%